2021
DOI: 10.3389/fimmu.2021.594858
|View full text |Cite
|
Sign up to set email alerts
|

A Plausible Role for Collectins in Skin Immune Homeostasis

Abstract: The skin is a complex organ that faces the external environment and participates in the innate immune system. Skin immune homeostasis is necessary to defend against external microorganisms and to recover from stress to the skin. This homeostasis depends on interactions among a variety of cells, cytokines, and the complement system. Collectins belong to the lectin pathway of the complement system, and have various roles in innate immune responses. Mannose-binding lectin (MBL), collectin kidney 1, and liver (CL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 110 publications
0
10
0
Order By: Relevance
“…However, it seems that MBL has dual effects in the regulation of skin inflammation. On the one hand, decreased MBL levels resulting from variant MBL2 polymorphisms are responsible for the progression of dermatomyositis and oral lichen planus, which might be attributed to the impaired clearance of apoptotic cells in the skin 17,19,20,25 . On the other hand, MBL exacerbated cutaneous burn injury and ischemia/reperfusion injury by facilitating inflammatory responses 34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it seems that MBL has dual effects in the regulation of skin inflammation. On the one hand, decreased MBL levels resulting from variant MBL2 polymorphisms are responsible for the progression of dermatomyositis and oral lichen planus, which might be attributed to the impaired clearance of apoptotic cells in the skin 17,19,20,25 . On the other hand, MBL exacerbated cutaneous burn injury and ischemia/reperfusion injury by facilitating inflammatory responses 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] In this study, the MBL level was significantly increased and showed a positive Mannan-binding lectin is a recognition molecule of the lectin complement pathway, and involved in microbial infection, the inflammatory response, and autoimmune diseases. 20 It is worth focusing on the diverse roles of MBL in the occurrence of skin diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations